Implementasi Kewajiban Mengikuti Sunnah Nabi Sebagai Pedoman Hidup Muslim - Puspita, Putri Indah; Cahyani, Audy Putri; Maulandari, Siti Diajeng Meva (CV. Kurnia Grup, 2025)
The obligation to follow the Sunnah of Prophet Muhammad ﷺ is one of the fundamental pillars of a Muslim’s life. The Sunnah serves as a practical guide that explains, complements, and applies the teachings of the Qur’an in various aspects of life. The implementation of this obligation extends beyond ritual worship, encompassing social, moral, and spiritual dimensions. This study aims to analyze the significance of implementing the Prophet’s Sunnah as a life guideline in shaping Muslims with noble character and a comprehensive Islamic worldview. The method used is a literature review, examining both classical and contemporary sources relevant to the topic. The results indicate that following the Sunnah of the Prophet is not merely an act of obedience, but also a path to achieving happiness in this world and the hereafter, as it reflects the perfection of faith and harmony between words, actions, and intentions. Therefore, the implementation of the obligation to follow the Prophet’s Sunnah should serve as the foundation for building character, social behavior, and an integrated Islamic way of life.